(untitled) (LEGAL DIALOGICA, 2025)
The legal basis for remote working in Indonesia still follows general labor regulations, which guarantee the rights of remote workers, including employment agreements, wages, leave, and social security. Although remote workers receive the same legal protections as conventional employees, more detailed regulations are needed to address the specific challenges of remote work. The growing trend of remote working in Indonesia highlights the need for more specific and comprehensive regulations from the government to clearly govern the rights and obligations of all parties, standards for work facilities, supervision mechanisms, and legal protection tailored to remote workers. These regulations aim to fill legal gaps and prevent potential violations of workers’ rights. Companies also play a crucial role in ensuring the protection of remote workers’ rights in accordance with applicable laws. This protection includes aspects such as wages, social security, occupational safety, as well as privacy and personal data. To ensure that remote working relationships remain fair and secure, company policies must refer to the Manpower Law and the Personal Data Protection Law. Abstrak: Landasan hukum kerja jarak jauh di Indonesia masih mengikuti regulasi ketenagakerjaan secara umum, yang menjamin hak pekerja remote seperti perjanjian kerja, upah, cuti, dan jaminan sosial. Meski mendapat perlindungan hukum yang sama dengan pekerja konvensional, diperlukan aturan lebih rinci untuk mengatasi tantangan spesifik kerja jarak jauh. Perkembangan sistem kerja remote working yang semakin meluas di Indonesia mendorong perlunya regulasi yang lebih spesifik dan komprehensif dari pemerintah guna mengatur secara rinci hak dan kewajiban para pihak, standar fasilitas kerja, mekanisme pengawasan, serta perlindungan hukum khusus bagi pekerja jarak jauh, sehingga dapat mengatasi kekosongan hukum dan mencegah potensi pelanggaran hak-hak pekerja. Perusahaan juga berperan penting dalam melindungi hak-hak pekerja jarak jauh sesuai ketentuan hukum yang berlaku. Perlindungan ini mencakup aspek upah, jaminan sosial, keselamatan kerja, serta privasi dan data pribadi. Agar hubungan kerja jarak jauh berjalan adil dan aman, kebijakan perusahaan harus mengacu pada Undang-Undang Ketenagakerjaan dan Undang-Undang Perlindungan Data Pribadi.